Sociopragmatic Analysis Of Presuppositions In Jerome Polin's Youtube Content - Linta Diana Fitri (International Journal of Education, Vocational and Social Science, 2025)
This study aims to analyze the forms and types of presuppositions in Jerome Polin's YouTube video content using sociopragmatic studies. Language not only functions as a means of communication, but also reflects social reality and relationships between individuals. In this context, presupposition is seen as a pragmatic aspect that contains implicit meanings based on shared assumptions between speakers and interlocutors. The method used is descriptive qualitative with data collection techniques in the form of listening, note-taking, and bibliography. The data were taken from a video entitled "Shock.. This Girl Graduated from High School at 14, Already a Doctorate at 20! Memorized 1000 Numbers of Pi!? Jerome Speechless". The results show that in the video there are four types of presuppositions, namely existential with 2 data, lexical with 1 data, structural with 13 data, and factive with 3 data. Meanwhile, nonfactive and counterfactual presuppositions were not found. This finding indicates that presuppositions in YouTube content not only clarify messages, but also build social closeness, and demonstrate the function of language in the context of digital communication. This research shows that sociopragmatic studies have important relevance in analyzing utterances in social media such as YouTube as a form of modern discourse